Teaching social justice: developmental considerations - Krafchick, Jennifer L., author; Kees, Nathalie, advisor; Zimmerman, Toni Schindler, advisor; Banning, James, committee member; Griffin, Cindy, committee member (Colorado State University. Libraries, 2007)
In a society that is growing more diverse each year, integrating diversity into the classroom is becoming more imperative. Educators at all levels who want to integrate content that addresses social justice issues related to gender, race, or class must compete with other curricular challenges. Being informed of developmental opportunities and challenges with young people of different ages can allow teachers to be more efficient and effective in teaching about diversity. An ethnographic content analysis was conducted with educators who elected to learn how to integrate a social justice curriculum entitled "FAIR: Fairness for all individualized through Respect" into their classrooms. One hundred educators participated in one-day conferences on integrating social justice into their classrooms and the FAIR curriculum. Educators completed survey and questionnaire evaluation data. An inductive analysis of these data was conducted to identify developmentally relevant themes for both students and teachers. Findings indicate that students in fourth, fifth, and sixth grades (ages seven through eleven) are ideally poised to learn about social justice issues, in addition the academic structure of elementary schools are better able to accommodate the integration of social justice content than at the junior high or high school levels. In addition, the development of social justice educators appears to be strongly influence by exposure to diversity, opportunities for self-reflection, and support from other social justice educators. Results from this study are consistent with the literature calling for greater multicultural training to prepare all educators to address diversity and social justice in their educational settings. Overall, educators felt that the FAIR curriculum was beneficial and effective for helping students learn about social justice issues, and that certain activities were more ideally suited for students at different developmental stages. Program evaluation information of the FAIR curriculum also yielded constructive guidance on continued development of the FAIR activities and supplemental information to provide to educators via the FAIR website (http://www.fair.cahs.colostate.edu/) that could be useful in adapting the curriculum for students at different developmental stages.
Keywords: women's studies; teacher education; minority and ethnic groups; sociology; ethnic studies